Peranan Penempatan Kerja dan Lingkungan Kerja Fisik dalam Meningkatkan Kinerja Karyawan Pada Industri Kuliner - Fhadillah, Muhammad Adhadhi (Journal of Business Management Education (JBME), 2020)
The problem of low employee performance that occurs in the CV. A because the attitude of employees who often absent from work, often delaying work so that it does not finish on time which results in decreased performance, and the division of hours based on shifts is less effective because the division of schedules based on shifts is not in accordance with applicable rules. In addition, the number of employees who are often absent, arriving late or leaving earlier than their working hours, this shows that the performance in this company is still low. This study aims to determine the effect of work placement on employee performance and the influence of the physical work environment on employee performance. As for the unit of analysis in this study is the culinary industry. The research method used in this study is quantitative. Retrieval of data by distributing questionnaires directly. The results showed that the effect of work placement on employee performance by 78.1% included in the strong category and the influence of the physical work environment on employee performance by 61.6% included in the strong category. This shows that the better the work placement and physical work environment, the higher the employee's performance. This means that if the work placement and physical work environment are good then optimal work output will be obtained, so that employee performance can improve properly. Maintaining employee performance is an important thing to do because if employee performance is low it will have a negative impact on the CV. A such as decreased work productivity, absenteeism is high and will have an impact on commitment while job satisfaction